DETECTION OF LITHOLOGICAL BOUNDARIES USING SECOND ORDER VERTICAL DERIVATIVES OF AEROGRAVITY DATA; A CASE OF HADEJIA SEGMENT OF THE CHAD BASIN, JIGAWA STATE NIGERIA - ALHASSAN, AHMAD; YUSUF IDI, BELLO; NASIR, MAHARAZ M; USMAN, NURADDEEN; HUSSAINI, ABDULLAHI; BALA, NASIRU; IBRAHIM, AUWAL; YAKUBU, NASIRU; AYUBA, IBRAHIM (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
Gravity method of geophysical prospecting is very effective in delineating geologic formations of based on the formation’s density contrast. In this work, a second vertical derivative of gravity data was used to delineate the boundary between two geologic formations of significant contrast in formation density. The study area is within the Hadejia arm of the contact region between the Chad sedimentary formation and the crystalline basement complex in the Northeastern Jigawa state of northern Nigeria. Satellite gravity data of the area which lies between latitude 110 -130E and longitude 80 - 140N was obtained from Bureau Gravimetrique International (BGI). The Bouguer correction was already applied on the data. Bouguer graph was plotted using surfer software. Second vertical derivative graph was also plotted. Low gravity anomalies are observed in the north with its minimum value appearing in the southwest. This suggests the existence of sedimentary rocks which are low in density, since sedimentary rocks are characterized by low density values. The result shows that second vertical derivative method is suitable for enhancing weaker local anomalies, defining the edges of geologically anomalous density disseminations and identification of geologic units.